Effect of Planting Media Composition and Synthetic Auxin ZPT on the Growth of Robusta Coffee Cuttings Grafting Seedling (Coffea canephora) - Adam Muhammad Ibrahim Musa; Gatot Subroto; Distiana Wulanjari; Dwi Erwin Kusbianto (Universitas Muhammadiyah Mataram, 2024)
Low coffee production and quality are two major problems of the Indonesian economy that must be addressed, especially in smallholder plantations. The use of Growth Regulators (ZPT) and Planting Media in coffee with the grafting method is expected to help in the growth of coffee plants. This study was designed using a Factorial Completely Randomized Design (CRD) consisting of 2 factors, namely ZPT Growtone Concentration (G0: Control, G1: 20/250 ml, G2: 25g/250 ml, G3: 30g/250 ml) and Composition of Planting Media Soil, Manure, and Sand (M0: Control, M1: 1:1:1, M2: 1:2:1, M3: 1:3:1). Each treatment was repeated three times. The parameters analyzed included plant height, number of roots, root length, root weight, stem diameter, and number of leaves. All data obtained in the study are presented in the form of tables and diagrams. The data obtained will be analyzed using analysis of variance (ANOVA). To test the effect of treatment on the observed variables, if there is a significant difference, the DMRT (Duncan Multiple Range Test) further test will be conducted at the 95% confidence level. The results showed that the combination of ZPT Growtone and Planting Media types of soil, manure, and sand had a significant effect on the number of branches parameter, and each factor also had a significant effect on the root length parameter. The best treatment is the combination of ZPT Growtone 20g/250 ml and Planting Media Composition 1:1:1. The treatment has the highest number of branches with an average of 2.67. The effect of the two factors on the grafting cuttings seedlings on the root length parameter was 16.83 and 16.96, respectively.